Epigenetics to Optogenetics A New Paradigm in the Study of Biology - Anwar, Mumtaz; Farooq, Zeenat; Ahmad Rather, Riyaz; Tauseef, Mohammad; Heinbockel, Thomas (Biochemistry, 2022)
Epigenetics, which deals with the study of heritable gene expression that takes place independent of changes in DNA sequence, and optogenetics, which deals with the study of genes expressed under the influence of light, are two emerging areas of study and research that have contributed immensely to our current knowledge of mechanisms and disease processes in humans. These disciplines are interrelated in the broader picture of biology and one can be used to change or modify the other. The complexity of the techniques involved in these disciplines often leads to a lack of proper understanding by researchers from other disciplines and the scientific community at large. As such, this book provides simple and easy-to-follow explanations of some of the most exciting areas of research in these disciplines.